IMMUNONTROPHYCAL EFFECT TO USE OF THE IMMUNOMODULATOR AND PROBYOTIC OF IN COMPLEX CURENCE OF SPECIFIC SURGICAL INFECTIONS - R. Kh. Gismatov; E. S. Galimova (Креативная хирургия и онкология)
The  application of  prebiotic   Bactisporin  and  immunomodulator Immureg   was  the subject  of the research. Immureg  and Bactisporin  were applied  as additional pathogenetic medications to  treat patients suffering from  active  tuberculosis and  secondary  syphilis. The use  of  the  medications aids to  increase  the  amount of  active  phagocytes in blood. Phagocytosis intensity  and  antimicrobial potential rise. The medications also stimulate TLymphocytic  component of  immune  system  and  regulate circulating  immune  complexes and IgM Immunoglobulin in blood.